Peri‐operative changes in diastolic function and outcomes in congenital aortic valve surgery. Issue 2 (11th January 2022) - Pesce, Meredith; LaPar, Damien; Kalfa, David; Bacha, Emile; Freud, Lindsay
Abstract: Background: The ratio of early diastolic mitral inflow velocity (E) to early diastolic mitral annular tissue velocity (e'), or E/e', is an echocardiographic measure of left ventricular filling pressure. Peri‐operative changes in E/e' and association with outcomes have been demonstrated in adults undergoing surgery for aortic stenosis (AS). We sought to explore changes in E/e' and other diastolic indices in the setting of congenital AS surgery and to assess for association with post‐operative outcomes among children and young adults. Methods: A retrospective, single‐center study was performed among patients 6 months to 30 years of age who underwent congenital AS surgery from 2006 to 2018. Tissue Doppler indices were collected from pre‐ and post‐operative echocardiograms. Post‐operative outcomes were reviewed. Results: Sixty‐six subjects with subvalvar (45%), valvar (47%), and supravalvar (8%) AS underwent surgery at a median age of 9.5 years (IQR: 4.0–14.8). Pre‐operatively, the lateral E/e' ratio was 8.6 (6.7–11.0); 33% had E/e'≥10. Post‐operatively, the lateral e' decreased to 9.9 cm/s (8.0–11.4), the E/e' ratio increased to 10.4 (8.3–13.1); and 53% had E/e'≥10 ( p ‐values < 0.0001, 0.0072, and < 0.001, respectively). Pre‐operative lateral e' correlated modestly with duration of intubation (ρ = −0.24, p ‐value 0.048) and post‐operative lateral e' correlated modestly with duration of intubation and length of hospital stay (ρ = −0.28 and −0.26, p ‐values = 0.02 and 0.04, respectively). Conclusions: Children and young adults who underwent congenital AS surgery had echocardiographic evidence of diastolic dysfunction pre‐operatively that worsened post‐operatively. Lateral e' may be a sensitive indicator of impaired ventricular relaxation in these patients and may impact duration of intubation and hospital stay.